Planejamento de capacidade com incerteza na demanda em unidades de distribuição de energia elétrica - Silva, Guilherme de Oliveira da (2019)
The service management system performance is closely related to the operational success. When considering electric power distribution systems, regulatory polices impose penalties and minimum service levels which demand a carefully observation on the available capacity. This work proposes a capacity planning approach involving uncertain demand by applying a stochastic linear programming model, in such a way that the maximum capacity is minimized. First, a probability distribution models are fitted to historical data to be further applied in random number generation, considering a large number of scenarios. From these numbers, a maximum capacity is obtained by using a deterministic linear programming model, specifically developed to include order deadlines and uncertain demand. Numerical results demonstrate how the proposed approach is suitable not only to have the final capacity level but also to study the variation on the initial inventory and its corresponding effect on the maximum capacity obtained.